FORMIST : a network to help training in Information literacy in France - Chevillotte, Sylvie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Information literacy has acquired /taking step by step/little by little a significant place position in the panorama of French universities over the past 10 years. It is organised in a very structured way, and it receives substantial state support. User training and the creation and broadcasting of educational documents is organised on a 3 level system: • local level: university libraries • regional level: seven URFIST (Unités Régionales de Formation à l’Information Scientifique et Technique) • national level: FORMIST (Réseau francophone de FORmation à l’Information Scientifique et Technique). FORMIST was introduced created in 1997 at ENSSIB (Ecole Nationale Supérieure en Sciences de l’Information et des Bibliothèques). FORMIST is a French website gathering educational tools, recommendations and information about information literacy (IL) and making them available to two kindskinds of communities: instructors (either teachers or library staff) and students. FORMIST also assumes the important role of coordinating an information instructors’ network, through colloquiums, workshops and instructing future librarians in teaching skills.